Karakteristik Struktur, Gugus Fungsi, dan Sifat Optik Karbon Arang Sekam Padi Terdoping Boron sebagai Material Fotovoltaik - Shafa Ainun Nabila (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
The transition toward sustainable energy systems has become increasingly important due to fossil fuel depletion and environmental concerns. Indonesia, as an equatorial country, receives abundant solar irradiation throughout the year, making photovoltaic technology a promising renewable energy source. In addition, Indonesia generates large amounts of rice husk biomass that can be utilized as a renewable and low-cost carbon precursor. This study investigates the synthesis of boron-doped amorphous carbon derived from rice husks for photovoltaic applications. The material was produced through traditional homemade pyrolysis followed by heat treatment, resulting in three sample variations (SM, S5, and S3). A leaching process was applied to reduce silica content, while boron doping was performed through wet mixing and thermal treatment in a furnace. The synthesized materials were characterized using XRD, FTIR, SEM–EDX, and UV–Vis spectroscopy. XRD results confirmed a predominantly amorphous carbon structure. FTIR analysis identified characteristic bonds including C=C, C–B, B–O, and residual Si–O, indicating successful boron incorporation. SEM observations revealed agglomerated particles with porous morphology, while EDX verified the presence of boron within the carbon matrix. UV–Vis analysis indicated that boron doping effectively reduced the band-gap energy of amorphous carbon compared to the intrinsic material. These findings demonstrate that boron doping improves the electronic and optical properties of rice husk-derived amorphous carbon, highlighting its potential as a sustainable and low-cost semiconductor material for photovoltaic applications.
Approved by Teddy
Keywords: NATURAL SCIENCES::Physics::Condensed matter physics::Semiconductor physics; energy